Techniques Display Data in A Visual Database Programming Language - Agung Brastama Putra; Siti Mukaromah; Mohamad Riza Ramadhani Oding; Muhammad Rizky Rahmatul Anam (Nusantara Science and Technology Proceedings, 2020)
Many techniques of presenting information in programming languages, mainly for data that amounts to less than 100 record data. Moreover, if the data has reached more than 10,000 data, application performance will slow down. This has several factors, one of which is the process or the way data is presented by the code/algorithm in a programming language. The purpose of this paper is to show the effects of comparisons of code/algorithms in presenting data, expected outcome of this comparison of code/algorithm is to demonstrate increasing code/algorithm can present data faster.